Influence of irradiation by a particle beam on optical properties of metal mirrors - Poperenko, L.V.; Vinnichenko, M.V.; Kosel, P.B.; Vinnichenko, K.L. (Functional Materials, 2005)
The surface of copper and stainless steel mirrors near the area destroyed by electron beam has been characterized by means of ellipsometric diagnostics. The treatment did not result in any changes in the surface microrelief, independent on the treatment duration, although changes in the ellipsometric parameters have been observed. According to the XPS data, these changes are due to disordering in the about 2 nm thick surface layer resulting from Ar ion implantation.